Penerapan Prinsip – Prinsip Good Corporate Governance Dalam Upaya Meningkatkan Kinerja Pada Perusahaan Perasuransian Badan Usaha Milik Negara (Studi Pada PT. ASABRI (Persero) Cabang Medan) - Vina Trinanda Dewi; Bismar Nasution; Sunarmi Sunarmi; Mahmul Siregar (Iuris Studia: Jurnal Kajian Hukum, 2021)
Good Corporate Governance (GCG) is an important instrument in doing business in a company. The aim of this study is to see how the relationship between the application of the principles of Good Corporate Governance and efforts to improve performance in Insurance Companies, what is the role of law in the meaning of laws and regulations, ensuring the application of good corporate governance principles in Insurance Companies, especially BUMN Insurance Companies (State-Owned Business Insurance Companies) and how to apply the principles of Good Corporate Governance at PT. ASABRI (Persero) as the efforts to improve company performance. This research method conducts normative legal research which is descriptive analysis. The data used consists of secondary data collected using library research techniques and primary data obtained through field research using interviews as a data collection technique. The data were analyzed using qualitative data analysis methods. Based on research at PT. ASABRI (Persero) Medan, the laws and regulations are considered not optimal in their implementations, and the principles of GCG have not been implemented properly